Factores que influyen en la medicación por madres a niños menores de 11 años, de la parroquia Sabanilla, cantón Celica. - González Morocho, Caroline María (2020)
The administration of drugs without medical prescription in infants is a social problem of great importance at present, it interferes in the natural evolution of diseases and makes it difficult to carry out an adequate and timely diagnosis. The aim of this study was to determine the prevalence of medication according to sex and age, the factors that influence it and the groups of drugs most used in children under 11 years of age in the Sabanilla parish. It was a quantitative and cross-sectional approach study; data collection was carried out by applying surveys to mothers of a total of 98 children. Obtaining as results that 85,70% of pediatric patients received drugs without a prescription, most frequently the male sex 52,30%, at ages 6 to 11 years 64,28%. The main factor that led to the medication was the lack of doctors in the parish 51,19%, followed by the ease of acquiring the drug in pharmacies and stores 47,61% and believing that signs and symptoms are not serious to consult the doctor 44,04%. The most widely used drugs were pain relievers / anti-inflammatory / antipyretic drugs (100%), anti-flu drugs (71,42%) and antibiotics (60,71%). The administration of medication in the pediatric population is high in this rural area, considering it a multifactorial problem, with high use of antibiotics that predispose to bacterial resistance at very young ages. Key words: self-medication, multifactorial problem, drugs.